Development of nutrient rich biofertilizer by co-vermistabilization of aquatic weeds using herbal pharmaceutical wastewater along with sediment of lake. (February 2021) - Dhadse, Sharda; Alam, Shahrukh Nawaj; Mallikarjuna Rao, M.
Abstract: Six aquatic weeds species namely Hydrilla verticilata (L.f.) Royle, Ceratophyllum demursum L., Nelumbo nucifera Gaerth., Ludwigia palustris L., Pistia stratioles L., and Eicchornia crassipis along with Eudrilus eugeniae (earthworm sp.) were selected for vermistabilization. Aquatic sediment, cow dung and microbes were taken in ratio 2:1:1 allowed up to 45 days for stabilization, the study claimed, newly developed vermicompost is a novel kind with a total NPK of 3.32%, 2.03%, 0.62% with enriched microbial flora. Pistia stratioles L. shown potential growth on plants. Graphical abstract: Unlabelled Image Highlights: The composition of composting material The characterization of developed vermicompost Heavy metal characterization of sediment, weeds, vermicompost and the earthworm The plant growth potential with developed vermicompost